SOUL THERAPY EFFORTS WITH DHIKR FOR TEACHERS AT TADIKA AL FIKH ORCHARD MALAYSIA SCHOOL - Zailani, Zailani; Fatimah Nur Fuad, Ai; Ruslan, Muhammad; Chapakiya, Suraiya (Berajah Journal, 2024)
This research aims to improve the quality of Tadika Al Fikh Orchard (Early Childhood Education) teachers in Islamic Religious Education learning. In the context of mental therapy, it should be done by integrating remembrance in every aspect of a person's life. This research involved the participation of Tadika Al Fikh Orchard Malysia teachers as research subjects. The results of this research show a significant increase in the personality quality of educators at Tadika Orchard Malaysia. Over time, these programs become an important part of students' lives, producing positive changes in the mental state of teachers that, in the long run, benefit individual students. The findings of this research provide practical implications in efforts to improve the quality of learning at Tadika Al Fikh Orchard Malaysia. Mental therapy efforts with remembrance for Tadika Al Fikh Orchard Malaysia teachers provide mental health for educators who in turn provide role models for Tadika Al Fikh Orchard Malaysia students. It is hoped that this research can become a basis for developing policies and programs that focus on improving teacher quality in terms of mental health.